Exploring marine mammal presence across seven US national marine sanctuaries - DeAngelis, Annamaria I.; Van Parijs, Sofie M.; Barkowski, Jack; Baumann-Pickering, Simone; Burger, Kourtney; Davis, Genevieve E.; Joseph, John; Kok, Annebelle C. M.; Kügler, Anke; Lammers, Marc; Margolina, Tetyana; Pegg, Nicole; et al. (Frontiers in Remote Sensing, 2022)
The United States of America’s Office of National Marine Sanctuaries (ONMS) hosts 15 National Marine Sanctuaries (NMS) and two Monuments in its waters. Charismatic marine megafauna, such as fin whales (Balaenoptera physalus), humpback whales (Megaptera novaeangliae), and various delphinid species frequent these areas, but little is known about their occupancy. As part of a national effort to better understand the soundscapes of NMS, 22 near-continuous passive acoustic bottom mounted recorders and one bottom-mounted cable hydrophone were analyzed within seven NMS (Stellwagen Bank, Gray’s Reef, Florida Keys, Olympic Coast, Monterey Bay, Channel Islands, and Hawaiian Islands Humpback Whale sanctuaries). The daily acoustic presence of humpback and fin whales across two years (November 2018 – October 2020) and hourly presence of delphinids over one year (June 2019 – May 2020) were analyzed. Humpback whales showed variability in their acoustic presence across NMS, but in general were mostly present January through May and September through December, and more scarce or fully absent June through August. Consecutive days of humpback whale vocalizations were greatest at sites HI01 and HI05 in the Hawaiian Islands Humpback Whale NMS and fewest at the Channel Islands NMS. Fin whales exhibited a similar seasonal pattern across the West Coast NMS and Stellwagen Bank NMS. Monterey Bay NMS had the greatest number of median consecutive presence of fin whales with fewest at Stellwagen Bank NMS. Delphinid acoustic presence varied throughout and within NMS, with sites at the Channel Islands and Hawaiʻi NMS showing the highest occupancy. All NMS showed distinct monthly delphinid acoustic presence with differences in detected hours between day versus night. Sixteen sites had medians of delphinid presence between one and three consecutive days, while three sites had five days or more of consecutive presence, and one site had no consecutive delphinid presence, showing clear variation in how long they occupied different NMS. Marine mammals utilized all NMS and showed a wide range of occupancy, emphasizing the importance of understanding species use across different NMS as biological areas for migration, breeding and foraging.